WHITE AND LESION‐MIMIC LEAF1, encoding a lumazine synthase, affects reactive oxygen species balance and chloroplast development in rice. (27th October 2021) - Hu, Haitao; Ren, Deyong; Hu, Jiang; Jiang, Hongzhen; Chen, Ping; Zeng, Dali; Qian, Qian; Guo, Longbiao
Summary: The riboflavin derivatives flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD) are essential cofactors for enzymes in multiple cellular processes. Characterizing mutants with impaired riboflavin metabolism can help clarify the role of riboflavin in plant development. Here, we characterized a rice ( Oryza sativa ) white and lesion‐mimic ( wll1 ) mutant, which displays a lesion‐mimic phenotype with white leaves, chlorophyll loss, chloroplast defects, excess reactive oxygen species (ROS) accumulation, decreased photosystem protein levels, changes in expression of chloroplast development and photosynthesis genes, and cell death. Map‐based cloning and complementation test revealed that WLL1 encodes lumazine synthase, which participates in riboflavin biosynthesis. Indeed, the wll1 mutant showed riboflavin deficiency, and application of FAD rescued the wll1 phenotype. In addition, transcriptome analysis showed that cytokinin metabolism was significantly affected in wll1 mutant, which had increased cytokinin and δ‐aminolevulinic acid contents. Furthermore, WLL1 and riboflavin synthase (RS) formed a complex, and the rs mutant had a similar phenotype to the wll1 mutant. Taken together, our findings revealed that WLL1 and RS play pivotal roles in riboflavin biosynthesis, which is necessary for ROS balance and chloroplast development in rice. Significance Statement: WLL1 and RS play pivotal roles in riboflavin biosynthesis, which is necessary for ROS balance and chloroplast development in rice.